2013
DOI: 10.1371/journal.pone.0082711
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Cystathionine β-Synthase and Cystathionine γ-Lyase During Acute Cholecystitis-Induced Gallbladder Inflammation

Abstract: BackgroundHydrogen sulfide (H2S) has recently been shown to play an important role in the digestive system, but the role of endogenous H2S produced locally in the gallbladder is unknown. The aim of this study was to investigate whether gallbladder possesses the enzymatic machinery to synthesize H2S, and whether H2S synthesis is changed in gallbladder inflammation during acute acalculous cholecystitis (AC).MethodsAdult male guinea pigs underwent either a sham operation or common bile duct ligation (CBDL). One, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…It is possible that CBS localizes to the plasma membrane during macrophagic attack to release H 2 S at the site of accumulation of oxidants released by macrophages. Our findings are supported by other studies that reported the localization of CBS in the plasma membrane of tissues from the gall bladder [35]. We, however, did not investigate the relative proportions of CBS distribution between the cytosol and the plasma membrane nor did we assess its localization in the mitochondrial fractions as is reported in colon cancer cells [32].…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that CBS localizes to the plasma membrane during macrophagic attack to release H 2 S at the site of accumulation of oxidants released by macrophages. Our findings are supported by other studies that reported the localization of CBS in the plasma membrane of tissues from the gall bladder [35]. We, however, did not investigate the relative proportions of CBS distribution between the cytosol and the plasma membrane nor did we assess its localization in the mitochondrial fractions as is reported in colon cancer cells [32].…”
Section: Discussionsupporting
confidence: 88%
“…The animals in the study groups were subjected to BDL. The animals in the BDL 24 h group and the BDL 48 h group were subjected to laparotomy and cholecystectomy at 24 and 48 h after surgery, respectively [12][13][14][15].…”
Section: Animals and Animal Experimentsmentioning
confidence: 99%
“…Cystathionine β synthase (CBS) is the best characterized H 2 S generating enzyme and this protein is considered to be the main source of H 2 S in the CNS (Abe and Kimura, 1996;Eto and Kimura, 2002;Miles and Kraus, 2004). However, it is also highly expressed in peripheral tissues, including the vasculature (Hosoki et al, 1997;Fiorucci et al, 2006;Zhang et al, 2013;Vellecco et al, 2016b;Szabo et al, 2013;Bucci et al, 2014). Another enzyme, cystathionine γ lyase (CSE or CGL or CTH), is the main H 2 S generating enzyme in the vascular system and is found in both endothelium and smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%